Characteristics, comorbidities, and outcomes of acute ischemic stroke cases treated with thrombolysis in Sanglah General Hospital Bali: A case series - Ida Ayu Sri Indrayani; Valentina Tjandra Dewi; Ida Bagus Kusuma Putra; I Gusti Ngurah Ketut Budiarsa; Nyoman Angga Krishna Pramana; Kumara Tini; I Made Oka Adnyana (Bali Anatomy Journal, 2021)
Background: Intravenous recombinant tissue plasminogen activator (IV rt-PA) in eligible patient groups is the main therapy for acute phase ischemic stroke within 4.5 hours of symptom onset which can significantly improve functional outcome. However, not all patients who underwent thrombolysis had a good outcome. Case: We report a series of seven patients cases undergoing IV thrombolysis from 2019-2020 at Sanglah General Hospital with varying baseline conditions and outcomes. Most cases benefit from IV rt-PA administration. There was one case with a poor outcome and one case with a rare anaphylactic reaction following alteplase administration. Conclusion: The number of thrombolysis procedure which is the main treatment of acute ischemic stroke is quite small. It is necessary to increase public education and understanding regarding the rapid response to acute stroke symptoms. Most of the cases yielded good outcomes while several cases had unfavorable outcomes related to variable factors. Hemorrhagic transformation does not directly associate with poor outcome. Clinicians also need to increase awareness of allergic reactions risk to rt-PA and provide prompt treatment.